Assessment of Greenhouse Gases Emission in Maize-Wheat Cropping System Under Varied N Fertilizer Application Using Cool Farm Tool - Kumar, Rakesh; Karmakar, S.; Minz, Asisan; Singh, Jitendra; Kumar, Abhay; Kumar, Arvind (Frontiers in Environmental Science, 2021)
Climate change induced by enhanced global warming is one of the biggest challenges at global level. Agriculture sectors significantly contribute to total anthropogenic greenhouse gases (GHG) emission to atmosphere. Wheat and maize, cultivated globally and consumed in different forms are considered as crucial staple cereal for ensuring food security to global population. The management practices involving ploughing, irrigation, fertilizer application, pest management etc. significantly influence the emission of carbon dioxide and nitrous oxide from agricultural soil. In our research study, we estimated the carbon dioxide and nitrous oxide emission from maize and wheat crops at four different levels of N fertilizer. Emissions of CO2 per hectare varied from 331.4 to 1088.3 kg CO2 and ranged from 292.3 to 765.3 kg CO2 in wheat on application of different doses of N. The total GHG emissions in maize crops ranged from 859.5 to 3003.4 kg CO2eq per hectare with the application of nitrogen at varying level (0-240 kg N per hectare). The highest N2O efflux (0.368 kg per tonne) was observed @ 240 kg N per hectare under wheat crop. The total on-farm emissions, through fertilizer production account for about 33.7%, and emission of N2O contributes only 65.9%, whereas, pesticides account merely 0.4% under maize-wheat cropping This study confirms that the direct emission of N2O was totally dependent on N fertilizers application rate, however, the indirect emission was controlled by the fuels and energy consumption.